Trade and diffusion of embodied technology: An empirical analysis - Stephen Ayerst; Faisal Ibrahim; Gaelan MacKenzie; Swapnika Reddy Rachapalli (Bank of Canada, 2023)
Using data from patents, citations, inter-sectoral sales and customs, we examine the international diffusion of technology through imports of sectoral knowledge and production inputs. We construct measures of the flow of technology embodied in imports. These measures are weighted by inter-sectoral knowledge and production input-output linkages that capture the relevance of this technology for generating new innovations in different sectors in importing countries. We develop an instrumental variable strategy to identify the causal effects of technology embodied in imports on innovation and diffusion outcomes. For sectors in importing countries, increases in both knowledge- and production-weighted embodied technology imports lead to technology diffusion (measured using backward citations in new patent applications) and increases in the rate of new innovations (measured using the forward citations those patents receive). Effects are substantially larger for knowledge-weighted imports of embodied technology, which also lead to improvements in the average quality of new innovations.
Keywords: O33; F14; O31; O19; F61; 330; Trade integration; International topics; Productivity; Development economics